Healthcare biotechnology : a practical guide - Dogramatzis, Dimitris, 1962- (Boca Raton, Florida : CRC Press, 2011)
'A first of its kind to focus on the management of health-care related biotechnology, this text is a resourceful practical guide that assists all healthcare related biotech professionals in their day-to-day activities. The book contains chapters on bioeconomy, biolicensing, biofinance, biopartnering, biodrug research, biomarketing planning, biopromotion, product life cycle management, and biobusiness models, among others. Written by a well-established professional and registered pharmacist, this reference is appropriate for graduate students and industry professionals. It contains over 350 tables and figures and end-of-section problems accompany each chapter. There are also extensive references following each chapter to enhance further study'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Pharmaceutical biotechnology; Biotechnology; Biotechnology industries; Biomedical Technology -- organization & administration